Demystifying marketing : a guide to the fundamentals for engineers - Forsyth, Patrick (IET management of technology series, 2007)
The book has 12 chapters and is divided into 4 parts. The first part deals with an overview of marketing; the second part covers fundamental issues of marketing; the third part covers strategy and marketing planning; and the fourth part covers marketing communication etc. An index is also given.